Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s00380-015-0653-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of idiopathic ventricular tachycardia originating above the pulmonary valve

Abstract: AbstractsPanoptic studies of ventricular tachycardia (VT) originating above the pulmonary valve are scarce. The purpose of this study is to clarify the characteristic of idiopathic VT arising above pulmonary valve. We analyzed 15 consecutive patients with idiopathic VT that was successfully abolished by catheter ablation at the right ventricular outflow tract (RVOT-VT, n = 11) and above the pulmonary valve (PA-VT, n = 4). Incidence of syncope was higher in PA-VT than RVOT-VT (100 % vs 27 %, P < 0.05) and polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Also, the incidence of syncope and polymorphic VT was high in all PA VT patients as compared to RVOT VT patients. 32 These findings showed that catheter ablation of RVOT-like VAs in PA is safe and efficacious, and PA is the potential novel site for catheter ablation in patients with RVOT-like VAs, which may contribute to the increased success rate of RFCA in the treatment of RVOT-like VAs.…”
Section: Successful Ablation In the Pamentioning
confidence: 75%
“…Also, the incidence of syncope and polymorphic VT was high in all PA VT patients as compared to RVOT VT patients. 32 These findings showed that catheter ablation of RVOT-like VAs in PA is safe and efficacious, and PA is the potential novel site for catheter ablation in patients with RVOT-like VAs, which may contribute to the increased success rate of RFCA in the treatment of RVOT-like VAs.…”
Section: Successful Ablation In the Pamentioning
confidence: 75%
“…However, with ventricular arrhythmias (VAs) originating from the RVOT, there have been reports of a few occurrences of cardiac events such as syncope or sudden cardiac death in pediatric patients 1,2 . Although cardiac complications are very rare in pediatric patients with VT arising from RVOT, the rapid excitation and conduction delays of ventricular arrhythmia originating above pulmonary valve appear to contribute polymorphic VT, suggesting its malignant electrophysiological characteristics 3,4 . We believed that this patient developed heart failure and arrhythmia‐induced cardiomyopathy because of the persistence of VT, which was at a relatively low heart rate with no accompanying palpitations, rather than frequent PVCs.…”
Section: Figmentioning
confidence: 90%